Controlling aluminum casting from stationary furnace - E. S. Kinev; A. A. Tyapin; E. A. Golovenko; Yu. S. Avdulova (Омский научный вестник, 2019)
The features of the combined induction device designed for transporting, pumping or mixing aluminum alloys with the possibility of its heating are considered. Heating is capable of melting aluminum plugs at the start, as well as compensating for heat losses during casting or melt mixing. The device is one of the varieties of linear MHD machines with a core and windings with a variable number of pole pairs and the sequence of switching windings is determined by the algorithm of the control unit modules. Due to the open configuration of the magnetic circuit of the MHD inductor asymmetry of the magnetomotive forces of the windings occurs, which leads to a distortion of the low-frequency running magnetic field. Evaluation of the asymmetry of the electromagnetic mode of the shortened machines for switching on the windings of six-zone inductors can be conveniently performed according to the vector diagrams of magnetic fluxes. Regulation of the force and intensity of heating of the induction MHD device is performed by redistributing the linear current load between the phases of the inductor or programming algorithms for separate control of the three-phase IGBT phase modes of the inverter operating at lower frequencies. With the correct choice of the winding connection scheme, the proposed device provides a continuous circular raster of flows in the cores, creating uniform traction forces and increasing the efficiency of electromagnetic effects.